The four dimensions of power : understanding domination, empowerment and democracy - Haugaard, Mark, 1961- (Manchester University Press, 2020)
In this accessible and sophisticated exploration of the nature and workings of social and political power, Mark Haugaard examines the interrelation between domination and empowerment. Building upon the perspectives of Steven Lukes, Michel Foucault, Amy Allen, Hannah Arendt, Anthony Giddens, Pierre Bourdieu and others, Haugaard offers a clear theoretical framework, delineating power in four interrelated dimensions.The first and second dimensions of power entail two different types of social conflict. The third dimension concerns tacit knowledge, uses of truth and reification. Drawing upon genealogical theory and accounts of slavery as social death, the fourth dimension of power concerns the power to create social subjects. The book concludes with an original normative pragmatist power-based account of democracy.Offering lucid and entertaining illustrations of complex theoretical perspectives, this book is essential reading for undergraduates, postgraduates and academics, while offering an indispensable guide for activists wishing to understand domination, resistance and empowerment.
Full-text access granted as courtesy of MUP during COVID-19 emergency.
Keywords: Power (Social sciences); Power (Social sciences) -- Political aspects.; Power (Social sciences) -- Psychological aspects.; Political science -- Philosophy.; Pouvoir (Sciences sociales); Pouvoir (Sciences sociales) -- Aspect politique.; Pouvoir (Sciences sociales) -- Aspect psychologique.; POLITICAL SCIENCE / History & Theory.; Political science -- Philosophy; Power (Social sciences) -- Psychological aspects